An in silico framework for the design and optimisation of bioinspired, 3D-printed, fibre-reinforced polymer heart valve leaflets - Hughes, Celia Elizabeth (Trinity College Dublin. School of Engineering. Discipline of Mechanical & Manuf. Eng, 2025)
Aortic stenosis is a disease of the aortic valve that carries a high risk of mortality if left untreated, and current prosthetic valve devices used for treatment have significant drawbacks such as the need for lifelong anticoagulant therapy or the risk of premature failure. Polymer heart valves have been proposed as a solution to this, offering the potential of extended durability and a reduction in the need for anticoagulant therapy. The aim of this thesis was to create a framework for the design, optimisation, and assessment of novel, bioinspired polymer leaflets to enable effective and efficient development of future devices. To achieve this, first extensive mechanical and image-based characterisation of native aortic valve leaflet tissue was conducted to establish a baseline for target mechanical properties and key microstructural features. Melt electrowriting (MEW) was identified as an additive manufacturing method to emulate the native leaflet structure, and through the embedding of this in a silicone polymer, enabled a tailored mechanical response. A finite element (FE) framework was developed to model the response of this composite material and assess its suitability for valve leaflets. Using this, the influence of fibre structure on leaflet response was demonstrated. Design of experiments (DOE) was used in tandem with the trileaflet model to establish the most effective structural combination of fibres and silicone for this leaflet. Further, a fibre reorientation algorithm was applied to optimise the reinforcement structure for this leaflet shape, and proved beneficial for leaflets under non-uniform loading. Finally, the translation of this work from simulation to benchtop was explored. This showed the success of manufacturing MEW mesh-embedded silicone and suggested future mechanical testing which should be performed on this material. It also highlighted the flexibility of manufacturing by successfully recreating one of the optimised fibre structures, showing the availability to integrate these materials into already existing valve manufacturing protocols. Overall, this work established an FE framework for the design and optimisation of fibre-reinforced polymer valve leaflets to enable the development of future polymer prosthetic devices.
APPROVED
Keywords: Finite element modelling; Melt electrowriting; Aortc stenosis; TAVR; Polymer valves